Chapter Sugar Beet Tolerance to Drought: Physiological and Molecular Aspects - Putnik-Delić, Marina (InTechOpen, 2018)
Drought often reduces sugar beet yield in the Balkan agroecological region. Climate forecasts indicate that this negative trend of drought periods will continue. Tolerance to drought is a complex trait, which comprises involvement of both physiological and molecular mechanisms in plants. This research was conducted on 11 sugar beet genotypes, which showed different tolerance to drought in the field. Experiment had three parts: water deficiency caused by cessation of watering conducted in the greenhouse, water deficiency imposed by different concentrations of polyethylene glycol on plants grown in tissue culture, and analysis of alterations in gene expression under drought. Plants exposed to stress in greenhouse had on average three leaves less, 4% lower water content, and seven-fold higher proline content. Classification of genotypes with respect to the level of tolerance to water deficiency on the basis of concentration of free proline, assessed in the experiment in vitro, corresponded to the result of the observation test in the field. Changes in the expression of candidate genes under drought suggest that one of them might be used for further development as a DNA-based marker. These results can be applied in sugar beet breeding aimed at increasing tolerance to water deficiency.